Effects of Different Environment-Friendly Gibberellic Acid Microcapsules on Herbicide Injury of Wheat - Zhang, Guisen; Ma, Tao; Cheng, Yong; Wang, Jianing; Liu, Lang; Zhang, Baojun (Frontiers in Plant Science, 2022)
Microcapsules are used more and more widely as an environmentally friendly dosage form.In order to clarify the effects of gibberellic acid microcapsule suspension on wheat herbicide, two types of microcapsule suspension were prepared by phase transfer method and in situ polymerization method, and the microcapsule size and encapsulation were determined Performance indicators such as rate and release rate; meanwhile, through field trials, the pharmacological and detoxifying effects of different types of microcapsule suspensions on the herbicide methyldisulfuron in wheat fields were compared. The results show that the microcapsules prepared by the two methods have a particle size of less than 10 μm, an encapsulation rate of more than 85%, a release rate in accordance with zero-order release kinetics in 0-4 days, and a first-order release kinetics in 5-28 days; The plot test showed that the detoxification effect of the microcapsules prepared by the in situ polymerization method was better than that of the microcapsules prepared by the phase transfer method and the control agent. The wheat growth index was higher than that of the blank control after using the agent.